Interleukin-27-dependent transcriptome signatures during neonatal sepsis - Povroznik, Jessica M.; Akhter, Halima; Vance, Jordan K.; Annamanedi, Madhavi; Dziadowicz, Sebastian A.; Wang, Lei; Divens, Ashley M.; Hu, Gangqing; Robinson, Cory M. (Frontiers in Immunology, 2023)
Human newborns exhibit increased vulnerability and risk of mortality from infection that is consistent with key differences in the innate and adaptive immune responses relative to those in adult cells. We have previously shown an increase in the immune suppressive cytokine, IL-27, in neonatal cells and tissues from mice and humans. In a murine model of neonatal sepsis, mice deficient in IL-27 signaling exhibit reduced mortality, increased weight gain, and better control of bacteria with reduced systemic inflammation. To explore a reprogramming of the host response in the absence of IL-27 signaling, we profiled the transcriptome of the neonatal spleen during Escherichia coli-induced sepsis in wild-type (WT) and IL-27Rα-deficient (KO) mice. We identified 634 genes that were differentially expressed, and those most upregulated in WT mice were associated with inflammation, cytokine signaling, and G protein coupled receptor ligand binding and signaling. These genes failed to increase in the IL-27Rα KO mice. We further isolated an innate myeloid population enriched in macrophages from the spleens of control and infected WT neonates and observed similar changes in gene expression aligned with changes in chromatin accessibility. This supports macrophages as an innate myeloid population contributing to the inflammatory profile in septic WT pups. Collectively, our findings highlight the first report of improved pathogen clearance amidst a less inflammatory environment in IL-27Rα KO. This suggests a direct relationship between IL-27 signaling and bacterial killing. An improved response to infection that is not reliant upon heightened levels of inflammation offers new promise to the potential of antagonizing IL-27 as a host-directed therapy for neonates.